Epidemiology of bronchiectasis - Mattia Nigro; Irena F. Laska; Letizia Traversi; Edoardo Simonetta; Eva Polverino (European Respiratory Review)
Bronchiectasis is a chronic respiratory disease characterised by permanent enlargement of the airways associated with cough, sputum production and a history of pulmonary exacerbations. In the past few years, incidence and prevalence of bronchiectasis have increased worldwide, possibly due to advances in imaging techniques and disease awareness, leading to increased socioeconomic burden and healthcare costs. Consistently, a mortality increase in bronchiectasis patient cohorts has been demonstrated in certain areas of the globe, with mortality rates of 16–24.8% over 4–5 years of follow-up. However, heterogeneity in epidemiological data is consistent, as reported prevalence in the general population ranges from 52.3 to more than 1000 per 100 000. Methodological flaws in the designs of available studies are likely to underestimate the proportion of people suffering from this condition worldwide and comparisons between different areas of the globe might be unreliable due to different assessment methods or local implementation of the same method in different contexts. Differences in disease severity associated with diverse geographical distribution of aetiologies, comorbidities and microbiology might explain an additional quota of heterogeneity. Finally, limited access to care in certain geographical areas is associated with both underestimation of the disease and increased severity and mortality. The aim of this review is to provide a snapshot of available real-world epidemiological data describing incidence and prevalence of bronchiectasis in the general population. Furthermore, data on mortality, healthcare burden and high-risk populations are provided. Finally, an analysis of the geographical distribution of determinants contributing to differences in bronchiectasis epidemiology is offered.